Catechol-chitosan/polyacrylamide hydrogel wound dressing for regulating local inflammation. (December 2022) - Lu, Bingyang; Han, Xiao; Zou, Dan; Luo, Xiao; Liu, Li; Wang, Jingyue; Maitz, Manfred F.; Yang, Ping; Huang, Nan; Zhao, Ansha
Abstract: Chronic wounds and the accompanying inflammation are ongoing challenges in clinical treatment. They are usually accompanied by low pH and high oxidative stress environments, limiting cell growth and proliferation. Ordinary medical gauze has limited therapeutic effects on chronic wounds, and there is active research to develop new wound dressings. The chitosan hydrogel could be widely used in biomedical science with great biocompatibility, but the low mechanical properties limit its development. This work uses polyacrylamide to prepare double-network (DN) hydrogels based on bioadhesive catechol-chitosan hydrogels. Cystamine and N, N′-Bis(acryloyl)cystamine, which can be cross-linking agents with disulfide bonds to prepare redox-responsive DN hydrogels and pH-responsive nanoparticles (NPs) prepared by acetalized cyclodextrin (ACD) are used to intelligently release drugs against chronic inflammation microenvironments. The addition of catechol groups and ACD-NPs loaded with the Resolvin E1 (RvE1), promotes cell adhesion and regulates the inflammatory response at the wound site. The preparation of the DN hydrogel in this study can be used to treat and regulate the inflammatory microenvironment of chronic wounds accurately. It provides new ideas for using inflammation resolving factor loaded in DN hydrogel of good biocompatibility with enhanced mechanical properties to intelligent regulate the wound inflammation and promote the wound repaired. Graphical abstract: Image 1 Highlights: Dual-response hydrogel drug delivery system was used to intelligently release drugs at inflammation area of chronic wound. DN hydrogel was designed to enhance the properties of chitosan-based hydrogel with two cross-linking agents. Resolvin E1 loaded into wound dressing can help to regulate wound inflammation by regulating macrophage behavior.